The assessment of the attitude of Sicilian consumers towards wild and farmed seafood products – a sample survey. Issue 7 (5th March 2021) - Allegro, Rosalinda; Calagna, Antonino; Lo Monaco, Daniela; Ciprì, Valentina; Bongiorno, Carmelo; Cammilleri, Gaetano; Battaglia, Luisa; Sadok, Saloua; Benfante, Viviana; Tliba, Ines; Di Bella, Calogero
Abstract : Purpose: The purpose of the paper was to know and evaluate consumption, preferences and the knowledge of labelling legislation about wild and farmed seafood products. Design/methodology/approach: A sample survey on Sicilian families was conducted through a direct interviews between October 2015 and October 2016 to study the attitudes of Sicilian consumers towards wild and farmed fish and seafood products. A stratified two-stage sampling design was chosen with variable probability of inclusion of the units of first stage and 1, 700 subjects were interviewed. Findings: The results obtained showed that the 69.4% of respondent ate fresh fish at least once a week and the 86% of respondents consumed aquaculture products at least once a month. Also, the 77.3% of respondents did not know the current legislation on the labelling. Multiple correspondence analysis allowed to identified three profiles of Sicilian families and binary logit model was used to examine the factors that influenced different frequency of fresh fish consumption in general and farmed seafood products in particular. Research limitations/implications: Extending the research throughout the Italian territory would have allowed further comparisons at the national level. Practical implications: The research provides useful information on Sicilian consumers that could be used by policymakers and by marketing communications company. Social implications: This research, on a restricted group of European consumers (Sicilian), characterised by living in an island, reinforce the knowledge regarding seafood consumers. Originality/value: This study used a probabilistic sampling design and a face-to-face questionnaire which produce results more robust in compare to surveys used more frequently such as non-probabilistic sampling design.